A rapid assessment of trends in the multispecies small-scale fishery of Palamós (Catalonia, Spain). (27th August 2015) - Dimitriadis, Caterina; Carranza, Alvar; Vilela, Raúl; Casadevall, Margarida
Abstract: Monitoring small-scale fisheries (SSFs) is challenging due to the limited information available and their underlying socioeconomic characteristics. This constitutes a serious impediment to assess the compliance level of Aichi Biodiversity Targets (ABT). The European Union has committed itself to include an Ecosystem Approach to Fisheries Management (EAFM) in its Common Fisheries Policy. EAFM depends on suites of indicators that track the pressure exercised, the state of the ecosystem, and the socio-economic consequences of management objectives. Therefore, The Living Planet Index (LPI) is proposed here for describing the performance of SSF towards the ABT. We show that the LPI can be reformulated to track trends in Fishing Effort ( LPIFE ), trends in Fish Populations ( LPIFP ), and both the state and trends related to the contribution of fisheries to broader society ( LPIDEB ). The implementation of the LPI in SSF applies several principles of the EAFM, including decentralization, fishers participation, and consideration of local knowledge. In this paper, we used 10-year daily data from the Cofradía at Palamós port, Catalonia - Spain. This is a multi-species SSF landing ca. 130 species, from which 10.9% are of special interest, being listed by the IUCN or in agreements by regional conventions. We observe a decreasing trend in the LPIFP, the LPIFE, and in the LPIDEB, including 36 species or groups, accounting for 90% of total landings, suggesting an overall decrease in the sustainability of this SSF. We conclude that use of the LPIFP is especially well suited to standardize the reporting of information for multispecies fisheries using a wide array of fishing strategies, and results strongly suggest the feasibility of using the LPI methodology to standardize reporting of any given agreed fisheries indicator in order enhance management towards the ABTs.